2004
DOI: 10.1021/ma035302a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Comblike Poly(butyl methacrylate) Using Reversible Addition−Fragmentation Chain Transfer and an Activated Ester

Abstract: Comblike polymers of poly(n-butyl methacrylate) were prepared using an activated estertype comonomer (N-acryloxysuccinimide, NAS) to generate branch points. The conventional solution freeradical copolymerization kinetics of n-butyl methacrylate (BMA) and NAS were first investigated by following individual monomer consumption rates by 1 H NMR spectrometry and reactivity ratios of BMA and NAS determined using the terminal model. The reactivity ratios so obtained are both close to 0.2; the joint confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 74 publications
1
49
0
1
Order By: Relevance
“…[11] In the absence of amino groups, conversion of active esters with hydroxy groups is possible, though elevated temperatures and activating agents such as N,N-dimethylaminopyridine may be required. [13] Polymers bearing NHS ester side chains can suffer from side reactions such as ring opening of the succinimide group and formation of N-substituted glutarimides by ring-closing attack of amides on neighboring active esters. [14] Suppression of these side reactions may be achieved by carrying out the post-polymerization reaction in DMSO at 75 8C for 24 h in the presence of five equivalents primary amine nucleophile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] In the absence of amino groups, conversion of active esters with hydroxy groups is possible, though elevated temperatures and activating agents such as N,N-dimethylaminopyridine may be required. [13] Polymers bearing NHS ester side chains can suffer from side reactions such as ring opening of the succinimide group and formation of N-substituted glutarimides by ring-closing attack of amides on neighboring active esters. [14] Suppression of these side reactions may be achieved by carrying out the post-polymerization reaction in DMSO at 75 8C for 24 h in the presence of five equivalents primary amine nucleophile.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Smith et al observed that the extent of grafting of an RGD peptide onto polyNAS decreased with increasing pH value and temperature owing to promotion of hydrolysis. [11] Cline and Hanna have noted that the reactivity of various amines towards aminolysis of p-nitrobenzoyl-Nhydroxysuccinimide in anhydrous dioxane correlated strongly with the basicity of the amino group, though steric hindrance within the investigated set of amines caused certain deviations [11,16] diNAS [8] NAS [18] NMAS [9,15,19] NAS [20] NSVB [20] NAS [4,13] NMAS [21,22] NSVB [23] NNHS [24] PFA [6] PFMA [6] PFVB [25] PFMA [26] NPF [7] NPA [27] NPMA [28] NPA [29] NPMA [30] MAPTT [10] 3 MA [17] MA [31] MA [32] MVI [17,33] VI [33] TMI [34] VDM [35,36] VDM [37] VDM [38] VPDMO [38] IDMO [38] GMA [39] GMA [40] 4-ES [41] GMA [42] GA [43] GMA …”
Section: Reviews 50mentioning
confidence: 99%
“…b) Polymerization in dispersed media. [67,122,336] Sty [67,69,122,336,337] MA [67,122,336,337] BuSSty [338,339] AA [340,341] MA b) [341] BA [338] a) [340] b) [341] DMAm [122] C 12 H 25 S-MMA [339] Sty [343] AA [341] BMA a) [342] MA [344] BA [123,345] b) [341] NAS a) [342] NIPAm [346] DMAm [343] …”
Section: Tbuo-mentioning
confidence: 99%
“…MMA [117,361] BMA [342] Sty [9] [67,69,336,337,349,[361][362][363][364][365] AA [248,323,[366][367][368][369][370] 4VP [364] MA [336,337,[361][362][363] BA [323,362] …”
Section: Tbuo-mentioning
confidence: 99%
“…Indeed, RAFT can be described as a molecular toolbox with which any desired polymer architecture can be created: in principle, one can place any monomer unit (and sequence of monomer units) anywhere on the chain, and even control branching structure. [24] Significant commercialization of the RAFT process must be through emulsion polymerization, to capitalize on advantages such as low viscosity at high conversion, readily controlled addition of any ingredient, absence of solvents, and direct use of the latex in surface coatings.…”
Section: Raft Polymerizationmentioning
confidence: 99%